Impact of public health emergency response to COVID-19 on management and outcome for stemi patients in beijing—a single-centre historic control study (2020)
Background: Coronavirus disease 2019 (COVID-19) pandemic poses great challenge on public health globally. Objective: To clarify the impact of COVID-19 pandemic on in-hospital management and outcomes for ST-segment elevation myocardial infarction (STEMI) patients in the non-epicenter. Methods and Results: We enrolled consecutive STEMI patients who visited Fuwai Hospital from January to March, 2020 (N=73) and also established a historical control including all consecutive STEMI patients in the same period of 2019 (N=95). The primary outcome was defined as a composite endpoint of all-cause death, heart failure, cardiac shock and cardiac arrest during hospitalization. Results: Emergency response for COVID-19 resulted in a significant 77.6% reduction in the number of primary percutaneous coronary intervention (PCI), and a trend towards higher rate of primary composite endpoint (15.1% vs. 11.6%, p=0.51). Conclusions: COVID-19 pandemic results in a significant reduction in emergent reperfusion therapy, and a trend towards higher in-hospital adverse events risk.